The spatial restructuring of competitive tennis in Germany - Meier, H. E.; Konjer, M.; Nagm, A. (German Journal of Exercise and Sport Research, 2017)
The paper explores the impact of the long-term demographic and economic changes Germany faces in competitive tennis. It is argued that demographic changes, rural restructuring, and urbanization serve to shrink the sociodemographic niche for middle- and upper-class sports in particular in rural regions. The idea is tested by analyzing data on competitive tennis teams from Hesse. The multilevel Poisson regression that was performed supports the idea that the development of competitive tennis teams is dependent on demographic and economic context factors although demographic factors dominate. Strong regional disparities are detected suggesting that competitive tennis is subject to a process of spatial restructuring. Methodological limitations and perspectives for further research are discussed. In dieser Arbeit wird untersucht, wie sich die langfristigen demografischen und wirtschaftlichen Veränderungen auf das Leistungstennis in Deutschland auswirken. Es wird postuliert, dass der demografische Wandel, die ländliche Restrukturierung und die Urbanisierung eine Schrumpfung der soziodemografischen Nische für Sportarten der Mittel- und Oberschicht bedingen, insbesondere im ländlichen Raum. Zur Überprüfung dieser These wurden Daten über Leistungstennismannschaften aus Hessen analysiert. Eine Mehrebenen-Poisson-Regression stützt die Annahme, dass die Entwicklung der Anzahl der Mannschaften im Leistungstennis von demografischen und wirtschaftlichen Kontextfaktoren abhängt, wenn auch demografische Faktoren dominieren. Es zeigen sich große regionale Ungleichheiten, die vermuten lassen, dass Leistungstennis einem Prozess der räumlichen Restrukturierung unterliegt. Methodische Einschränkungen und Perspektiven für zukünftige Forschungsarbeiten werden diskutiert.